Advancing Marine Engineering Literacy Through Green Technology Integration: Competency Development for Alternative Fuel Systems and Hybrid Propulsion - Mardiana; Pantjadjatmika Rachmardata; Arief Supriatna; Octi Avriani; Rikman Sohriadhana (Meteor STIP Marunda, 2025)
This study investigates the development of marine engineering literacy focusing on emerging green propulsion technologies including LNG, methanol, ammonia fuel systems, and hybrid electric propulsion. The research examines how marine engineering curricula can effectively integrate alternative fuel technology knowledge while maintaining traditional thermodynamic and mechanical engineering foundations. Through curriculum analysis and competency assessment across maritime academies, the study identifies critical literacy components required for future marine engineers to operate, maintain, and troubleshoot sustainable propulsion systems. The research addresses the urgent need for skilled marine engineers capable of supporting the maritime industry's transition toward IMO 2050 decarbonization targets. Findings offer comprehensive recommendations for updating marine engineering education to encompass green technology literacy.